Method for forming a crystalline or polycrystalline layer of an organic-inorganic metal halide perovskite

By converting 2D perovskite materials into 3D perovskite materials, the problem of insufficient perovskite film quality in the prior art has been solved, and efficient photovoltaic equipment performance has been achieved, especially in terms of crystallinity and photoelectric properties, which have achieved significant results. progress.

CN112840473BActive Publication Date: 2025-01-10OXFORD PHOTOVOLTAICS LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201980067239.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-24
Filing Date
2019-09-23
Publication Date
2025-01-10
Estimated Expiration
2039-09-23

AI Technical Summary

Technical Problem

The existing perovskite film preparation methods are difficult to obtain high-quality 3D HOP films, resulting in limited performance of photovoltaic equipment, especially in terms of improving crystallinity, morphology and density, and carrier life.

Method used

2D perovskite material is converted into 3D perovskite material by forming a two-dimensional perovskite material with a planar layered structure on the substrate and converting it into a high quality with a three-dimensional crystal structure through the reaction step. Perovskite films, using structural forms such as Ruddelsden-Popper, Aurivillius, Dion-Jacobson, etc., optimize the chemical and physical properties of the intermediate blocks to obtain an efficient 3D perovskite layer.

Benefits of technology

Perovskite materials with excellent three-dimensional crystallinity, improved morphology and photoelectric properties have been achieved, which significantly improves the performance of photovoltaic equipment, including improved charge carrier lifetime and higher photovoltaic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN112840473B_ABST
    Figure CN112840473B_ABST
Patent Text Reader

Abstract

The present invention provides a method for forming a crystal or polycrystalline layer of an organic-inorganic metal halide perovskite material, wherein the organic-inorganic metal halide perovskite material comprises a three-dimensional crystal structure represented by the formula AMX3, wherein A represents an organic cation or a mixture of two or more different cations, at least one of which is an organic cation, M represents a divalent metal cation or a mixture of two or more different divalent metal cations, and X represents the same or different halide anions, the method comprising the following steps: (i) forming a first layer on the surface of a substrate, the first layer comprising an organic-inorganic metal halide perovskite material having a planar, layered two-dimensional crystal structure; (ii) reacting the first layer with one or more organic halides to form a crystal or polycrystalline layer comprising an organic-inorganic metal halide perovskite material having the formula AMX3. A photovoltaic or photovoltaic device is also provided, comprising an active layer, the active layer comprising an organic-inorganic metal halide perovskite material, the organic-inorganic metal halide perovskite material comprising a three-dimensional crystal structure represented by the formula AMX3, wherein the material can be obtained using the method defined above.
Need to check novelty before this filing date? Find Prior Art

Description

Field of the Invention

[0001] The present invention relates to a method for preparing a layer of a three-dimensional perovskite material with improved crystallinity. The crystalline perovskite material of the present invention may show improved morphology and improved optoelectronic properties. The present invention also relates to optoelectronic devices and solar cells comprising a layer of a perovskite material prepared using the method. Background of the Invention

[0003] Solar energy conversion is one of the most promising technologies for providing renewable energy. However, the high cost of manufacturing devices that capture solar energy, including high material costs, has historically hindered its widespread use.

[0004] Under normal sunlight conditions, the efficiency of a material used in a photovoltaic device such as a solar cell is a function of the material's bandgap. If the bandgap is too high, most sunlight photons are not absorbed and are lost to transmission or reflection; if it is too low, most photons have much more energy than is required to excite an electron across the bandgap, and the rest will be lost to thermalization. The Shockley-Queisser limit refers to the theoretical maximum efficiency that can be obtained with a single-junction solar cell. The highest theoretical efficiency is about 33%, and is obtained with a 1.34 eV bandgap.

[0005] Even higher theoretical efficiencies can be achieved using tandem or multijunction cells with successively different bandgaps (see, for example, J. Nelson, The Physics of Solar Cells, pp. 297-309, Imperial College Press

[2003] ISBN-13978-1-86094-340-9).

[0006] One particularly promising class of materials for making solar cells is the metal halide perovskites (see Photovoltaic Solar Energy – from Fundamentals to Applications

[2017] , edited by Reinders et al. Wiley ISBN 9781118927465, especially Chapter 6.3). Three-dimensional (3D) perovskite materials have the general formula AMX3, where A and M are cations and X is an anion. Their structure is formed by a 3D network of MX6 that can be connected by corners, edges, or faces, with the A cations located in dodecahedral positions (12-fold environment) between the MX6 octahedra. Figure 1An example of a 3D perovskite with MX6 octahedra connected by corners is shown in Figure 1. The relative sizes of A, M, and X determine the stability of the perovskite and the symmetry of the particular crystal structure formed. Perovskites can more generally be considered as crystal structures that contain parts with a 3D perovskite structure.

[0007] Hybrid organic-metal halide perovskites (HOPs) are a subfamily of the perovskite family, where A is an organic cation or a mixture of organic and inorganic cations, M is a metal, typically Pb, Sn, Ge, Cu, Bi or mixtures thereof, and X is a halide, typically Cl, Br, I or mixtures thereof. Recently, thin film HOPs have been found to be very good materials for optoelectronic applications, especially as photovoltaic materials, because of their unique ability to act as both light-harvesting media and charge carrier transporters.

[0008] To date, HOP materials that employ a single-phase 3D structure with corner-connected BX6 octahedra have shown the highest performance in single-junction photovoltaic devices, with a conversion efficiency of 22.7% recorded in 2017. The first HOP that was found to be a good absorber for solar cells, CH3NH3PbI3 (MAPbI3), has been limited in commercialization due to stability issues. However, since then, alternative compositions with increased stability and high performance have been developed, such as (CH(NH2)2) 1-x Cs x PbI3(FA 1-x Cs x PbI3) and (FA,MA,Cs,Rb)1PbI3.

[0009] WO2016 / 194317 discloses a method for forming a perovskite film by inducing a chemical reaction between a metal halide compound and methylamine gas. The method comprises forming a metal halide film on a substrate, then exposing it to methylamine gas to induce a reaction to form a perovskite, which can be further processed by simultaneously or continuously exposing it to gaseous hydroiodic acid and gaseous methylamine.

[0010] CN108539025 discloses a highly oriented two-dimensional hybrid perovskite film and a preparation method thereof. The perovskite film is a two-dimensional sheet-like film with high orientation and a thickness of 400-450 nm, and is prepared by obtaining two-dimensional tin oxide nanosheets with high crystallinity produced by conductive glass immersed in tin chloride, and depositing a perovskite film thereon.

[0011] US2018 / 0247769 discloses a method for forming a lead-free perovskite film based on vacuum evaporation, the method comprising depositing a first tin halide material on a substrate to form a first layer, and then depositing a second organic halide material on the first layer to form a second layer to obtain two layers of sequentially deposited films on the substrate. It is then annealed to induce interdiffusion of the layers to form the desired perovskite film.

[0012] US2016 / 0049585 discloses a method for manufacturing a perovskite solar cell, wherein a hole transport layer is formed on a transparent conductive substrate, and a perovskite layer is formed thereon by a two-stage vacuum evaporation process. Thereafter, an electron transport layer and an electrode layer are formed in sequence. The two-stage vacuum evaporation includes vacuum evaporating a first material on the hole transport layer, and then vacuum evaporating a second material so that the first material reacts with the second material in situ to form a perovskite layer.

[0013] The quality of perovskite films is critical to the performance of devices and is greatly affected by the method used to make the films. Common routes for making 3D HOP films for optoelectronic applications fall into two major categories: so-called 1-step or 2-step methods. The 1-step method involves a material deposition stage to form a 3D perovskite directly on a substrate. The 2-step method involves a material deposition stage to form a precursor metal-halide such as PbI2 or a metal-halide-organic complex (e.g., PbI2-dimethyl sulfoxide or PbI2-thiourea) film on a substrate, followed by a second material deposition stage and converting the precursor layer into a perovskite layer with a three-dimensional crystal structure. Each of these methods can be implemented using chemical deposition from solution or physical or chemical vapor deposition, or a combination of the two for the 2-step method. Both methods may involve additives, the use of different atmospheres, and the use of heating steps to optimize the final perovskite film. The highest efficiencies previously reported came from the 2-step method.

[0014] Therefore, an object of the present invention is to provide a novel method for preparing 3D HOP thin films. The method produces higher quality films, for example, higher quality films with increased crystallinity, improved morphology, higher density, larger grain size, and long support life. SUMMARY OF THE INVENTION

[0016] According to a first aspect of the present invention, there is provided a method of forming a crystalline or polycrystalline layer of an organic-inorganic metal halide perovskite material comprising a three-dimensional crystal structure represented by the formula AMX3.

[0017] According to a second aspect of the present invention, there is provided an optoelectronic or photovoltaic device comprising an active layer comprising an organic-inorganic metal halide perovskite material, wherein the organic-inorganic metal halide perovskite material comprises a three-dimensional crystal structure represented by the formula AMX3,

[0018] wherein A represents an organic cation or a mixture of two or more different cations, at least one of which is an organic cation,

[0019] M represents a divalent metal cation or a mixture of two or more different divalent metal cations,

[0020] and X represents the same or different halide anions,

[0021] The material may be obtained by the method according to the first aspect of the present invention.

[0022] The method utilizes a 2-step process of metal-halide or metal-halide organic complex alternative precursor films that can be converted into the final 3D perovskite. The new precursors are planar layered perovskite materials with a two-dimensional (2D) crystal structure, which we define below. Using the method of the present invention, this type of 2D hybrid organic-metal halide perovskite film is converted into an exceptionally high quality organic-metal halide perovskite film with a three-dimensional (3D) crystal structure.

[0023] 2D perovskites are a family of perovskites, where the layers of 3D perovskites are separated by interlayers, Figure 3 Some examples are shown in . For 2D HOPs, the interlayer consists of an organic block, where the organic block may contain some inorganic ionic components or substitutions. The 2D HOPs of interest are those with a perovskite layer of corner-connected MX6 octahedra, which are structurally similar to the 3D HOP films that currently show the highest performance in solar cells.

[0024] In a preferred embodiment, the planar layers of the 2D perovskite are oriented perpendicular to the normal to the surface of the substrate on which the planar layers are deposited.

[0025] The perovskite layer in 2D perovskite can have Figure 4 A different number of AMX3 slabs (n) as shown, and / or Figure 3 Different orientations of the axes along which these layers separate are shown. Depending on the chemical and physical properties of the interlayer organic blocks and their relative position between the perovskite (AMX3) layers, a variety of different structural forms of 2D perovskite materials can be obtained, such as:

[0026] a). “Ruddelsden-Popper perovskite” (RP), Figure 3 (a), having the general formula A'2A n-1 M n X 3n+1A family of materials wherein A is a cation in the 12-fold environment within the perovskite sheet, A' is a cation separating the 2D layers (interlayer cations), M is a cation at the 6-fold position within the perovskite layer, and X is an anion at the 9-fold position within the perovskite layer. A and A' can be the same or different cations, A can also be the only cation or a mixture, A' can be the only cation or a mixture, X can be the only anion or a mixture, and M can be the only cation or a mixture. Figure 4 The n=1, n=2 and n=3 members of the Ruddelsden-Popper family are shown, where n is an integer defining the number of AMX sheets in each 2D perovskite layer.

[0027] b). "Aurivillius perovskite", Figure 3 (b) having the general formula A'2A n-1 M n X 3n+3 , wherein the organic interlayer block has the formula A'2X2. A, M and X are as defined above. A' can be the only cation or a mixture, but cannot be the same as A.

[0028] c). "Dion-Jacobson Perovskite", Figure 3 (c) having the general formula A'A n-1 M n X 3n+1 , wherein the organic block is formed by an organic molecule A' different from A.

[0029] For these first three examples, the perovskite layers (for a given n) remain identical to each other, as Figure 3 As shown, the perovskite layers are parallel to the {100} crystal direction.

[0030] The fourth group "{110} parallel perovskite", Figure 3 (d) having the general formula A'2A n M n X 3n+2 It is also shown where the perovskite layers are parallel to the {110} crystal direction rather than the {100} crystal direction and the organic interlayer is formed by A′ cations, which are defined in the same way as the Ruddlesden Popper perovskite.

[0031] The above 2-D perovskite examples do not include an exhaustive list - other families exist and can be used in the present approach - such as interlayers in the described {110} parallel perovskites that look like Aurivillius or DJ interlayers or interlayers with different stacking orientations.

[0032] The object of the present invention is to provide an organic-inorganic metal halide perovskite material having excellent three-dimensional crystallinity, improved morphology, improved optoelectronic properties and excellent photovoltaic performance. Compared with other reported 3-D perovskite crystals, the improved perovskite material prepared by the method of the present invention exhibits improved crystallinity, reduced (and preferably no) grain boundaries, smooth texture, large grain size and a generally flat surface. The present invention also provides improved crystalline 3-D perovskite materials having potentially higher stability than 3-D perovskite materials prepared using existing methods. As a result, these materials can be used to prepare photovoltaic devices with improved properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The present invention will now be described in more detail, by way of example only, and with reference to the accompanying drawings, in which:

[0035] Figure 1 The conversion of a 2D perovskite structure into a 3D perovskite structure with MX6-cornered octahedra is shown;

[0036] Figure 2A A schematic diagram showing the process flow of the method of the present invention;

[0037] Figure 2B A schematic diagram showing an alternative method flow of the present invention;

[0038] Figure 3 (a)-(d) show Ruddlesden Popper, Aurivillius, Dion-Jacobson and {110} parallel 2D perovskites with n=2;

[0039] Figure 4 (a)-(c) show n=1, n=2 and n=3 members of the Ruddelsden-Popper 2D perovskite family and {110} parallel-type 2D perovskites;

[0040] Figure 5 XRD patterns of the same 2D perovskite material prepared by different routes are shown; (a) conversion by spin coating a solution containing A' cations on a metal halide precursor layer, (b) conversion by a chemical bath in a solution containing A' cations of the metal halide precursor layer, and (c) 1-step formation of the 2D material by spin coating a solution containing metal halide and A' cations;

[0041] Fig. 6A showing overlaid XRD patterns of 3D perovskite materials i) prepared using the method of the present invention, and ii) prepared using a two-step prior art method;

[0042] Figure 6BThe full width at half maximum (FWHM) and the number of counts of the 3D perovskite material prepared by the method of the present invention are shown;

[0043] Figure 6C Showing the full width at half maximum (FWHM) and number of counts for 3D perovskite materials prepared by a two-step prior art method;

[0044] Figure 7 (a) shows XRD patterns of three 3D perovskite films with three different ratios of halide anions Y:Z prepared using the method according to the present invention;

[0045] Figure 7 (b) shows UV-visible spectra of the same three films;

[0046] Figure 8 (a) shows two atomic force microscope (AFM) images of a 3D perovskite material prepared using the method according to the present invention;

[0047] Figure 8 (b) shows two atomic force microscope (AFM) images of a 3D perovskite material prepared using a two-step prior art method;

[0048] Fig. 9 (a) shows a top view (upper) and a cross-sectional view (lower) generated from a scanning electron microscope (SEM) image of a 3D perovskite material prepared using the method according to the present invention;

[0049] Fig. 9 (b) shows a top view (upper) and a cross-sectional view (lower) generated from a scanning electron microscope (SEM) image of a 3D perovskite material prepared using a 2-step prior art method;

[0050] Fig.10 Shown are overlaid photoluminescence measurements of 3D perovskites i) prepared using the method of the present invention (grey) and ii) prepared using a two-step prior art method (black);

[0051] Fig.11 showing overlaid time resolved photoluminescence (TRPL) measurements showing the charge carrier lifetime of a 3D perovskite material prepared using the method of the present invention compared to a 3D perovskite material prepared using a 2-step prior art method;

[0052] Fig. 12A shows overlaid X-ray diffraction patterns of 3D perovskite materials obtained using the method of the present invention involving direct chemical deposition of 2D materials with A'=arylammonium ions (grey) or A'=alkylammonium ions (black);

[0053] Fig. 12B shows the XRD of a perovskite prepared according to the method of the present invention in which there is no second halide deposition step;

[0054] Fig.13 Figure 2 shows the current-voltage scans of single junction devices prepared via the 2D route and the 2-step method, where we see a Voc gain via the 2D route, as expected from the higher PLQE.

[0055] Fig.14 Schematic diagram showing the overall process flow of a method using the method of the present invention and the overall process flow of a 2-step prior art method. DETAILED DESCRIPTION OF THE INVENTION

[0057] definition

[0058] As used herein, the term "photoactive" refers to an area, layer or material that is capable of photoelectrically responding to light. Thus, a photoactive area, layer or material is capable of absorbing energy carried by photons in light, which energy then results in the generation of electricity (e.g., by generating electron-hole pairs or excitons).

[0059] As used herein, the term "perovskite" refers to a material having a three-dimensional crystal structure related to the crystal structure of CaTiO3 or a two-dimensional material comprising a layer of material having a structure related to the structure of CaTiO3. The structure of CaTiO3 can be represented by the formula AMX3, wherein A and M are cations of different sizes, and X is an anion. In the unit cell, the A cation is (0,0,0), the M cation is (1 / 2,1 / 2,1 / 2), and the X anion is (1 / 2,1 / 2,0). The A cation is generally larger than the M cation. The skilled person will understand that when A, M and X are changed, the different ion sizes can cause the structure of the perovskite material to be distorted from the structure adopted by CaTiO3 to a distorted structure of lower symmetry. If the material is in the form of a layer having a structure related to the structure of bulk CaTiO3, the symmetry will also be lower. The materials of the layer comprising the perovskite material are well known. For example, K2NiF4 perovskite adopts an n=1RP structure (as defined in the introduction). The skilled person will appreciate that the perovskite material can be represented by the formula [A][M][X]3, where [A] is at least one cation, [M] is at least one cation, and [X] is at least one anion. When the perovskite contains more than one A cation, the different A cations can be distributed on the A positions in an ordered or disordered manner. When the perovskite contains more than one M cation, the different M cations can be distributed on the M positions in an ordered or disordered manner. When the perovskite contains more than one X anion, the different X anions can be distributed on the X positions in an ordered or disordered manner.

[0060] As described in the preceding paragraph, as used herein, the term "perovskite" refers to (a) a material having a three-dimensional crystal structure related to the crystal structure of CaTiO3, or (b) a material comprising a layer of a material, wherein the layer has a structure related to the CaTiO3 structure. Although both types of perovskites can be used in devices, in certain circumstances, it is preferred to use the first type of perovskite, (a), i.e., a perovskite having a three-dimensional (3D) crystal structure. The two types of perovskites have been described in detail in the Introduction ( Figure 1 , 3 and 4). 2D layered perovskites tend to have high exciton binding energies, which favor the generation of bound electron-hole pairs (excitons) rather than free charge carriers under photoexcitation. Bound electron-hole pairs may not be able to move sufficiently to reach p-type or n-type contacts, where they can then transfer (ionize) and generate free charges. Therefore, in order to generate free charges, the exciton binding energy must be overcome, which represents the energy cost of the charge generation process and results in lower voltage and lower efficiency in photovoltaic cells. In contrast, perovskites with 3D crystal structures tend to have much lower exciton binding energies (on the order of thermal energy), and can therefore generate free carriers directly after photoexcitation. Therefore, the perovskite semiconductor used in the devices and methods of the present invention is preferably a first-class perovskite, (a), i.e., a perovskite with a three-dimensional crystal structure, particularly when the optoelectronic device is a photovoltaic device such as a solar cell.

[0061] The 3D perovskite material prepared using the method of the present invention has the general formula (I):

[0062] [A][M][X]3(I)

[0063] wherein [A] is an organic cation or a mixture of two or more different cations, at least one of which is an organic cation; [M] is a divalent metal cation or a mixture of two or more different divalent metal cations; and [X] is one or more halide anions.

[0064] [X] preferably comprises one or more halide anions selected from fluoride, chloride, bromide and iodide, and preferably selected from chloride, bromide and iodide. [X] more preferably comprises one or more halide anions selected from bromide and iodide. In some embodiments, [X] preferably comprises two different halide anions selected from fluoride, chloride, bromide and iodide, and preferably selected from chloride, bromide and iodide, and more preferably comprises bromide and iodide.

[0065] Preferably, [A] is selected from one or more monovalent cations. [A] preferably comprises one or more selected from methylammonium (CH3NH3 + ), carboxamidinium (HC(NH)2)2+ ) and an organic cation of ethylammonium (CH3CH2NH3 + ), and preferably contains an organic cation selected from methylammonium (CH3NH3 + ) and formamidinium (HC(NH)2)2 + ). [A] may contain one or more inorganic cations selected from Cs + , Rb + , Cu + , Pd + , Pt + , Ag + , Au + , Rh + and Ru + .

[0066] [M] preferably contains at least one divalent inorganic cation selected from Pb 2+ and Sn 2+ , and preferably contains Pb 2+ .

[0067] In a preferred embodiment, the perovskite material has the following general formula:

[0068] A x A’ 1-x M(X y X’ 1-y )3(IA)

[0069] where A is formamidinium (FA), A’ is cesium cation (Cs + ), M is Pb 2+ , X is iodide, and X’ is bromide, and where 0 < x ≤ 1 and 0 < y ≤ 1. In these preferred embodiments, the perovskite material can thus contain a mixture of two monovalent cations. Additionally, in preferred embodiments, the perovskite material can thus contain a single iodide anion or a mixture of iodide anions and bromide anions. The inventors have found that such perovskite materials can have a band gap ranging from 1.50 eV to 1.75 eV, and layers of such perovskite materials with a suitable crystal morphology and phase can be easily formed. More preferably, the perovskite material is FA 1-x Cs x PbI 3-y Br y .

[0070] The perovskite material employed in the present invention is a material that is capable of absorbing light and thereby generating free charge carriers. Thus, the perovskite employed is a perovskite material that absorbs light. However, the skilled person will appreciate that the perovskite material may also be a perovskite material that is capable of emitting light by receiving charges—both electrons and holes—that subsequently recombine and emit light. Thus, the perovskite employed may be a light-emitting perovskite used in a light-emitting device.

[0071] The perovskite material prepared in this invention is crystalline or polycrystalline, ie, composed of more than one type of crystal.

[0072] As will be appreciated by the skilled person, the perovskite material employed in the present invention may be a perovskite that acts as an n-type electron transport semiconductor when light doped. Alternatively, it may be a perovskite that acts as a p-type hole transport semiconductor when light doped. Therefore, the perovskite may be n-type or p-type, or it may be a nominally intrinsic semiconductor. In a preferred embodiment, the perovskite employed is a perovskite that acts as an n-type electron transport semiconductor when light doped. The perovskite material may exhibit bipolar charge transport, and therefore acts as both an n-type semiconductor and a p-type semiconductor. Specifically, depending on the type of junction formed between the perovskite and the adjacent material, the perovskite may act as both an n-type semiconductor and a p-type semiconductor.

[0073] Typically, the perovskite semiconductor used in the present invention is a photoactive material, ie, a material capable of performing photogeneration and charge transport.

[0074] As used herein, the term "mixed anion" refers to a compound comprising at least two different anions. The term "halide" refers to an anion of an element selected from Group 17 of the periodic table, i.e., an anion of a halogen. Typically, a halide anion refers to a fluoride anion, a chloride anion, a bromide anion, an iodide anion, or an astatide anion. The perovskite compound defined herein may have more than one halide anion. Suitable combinations of halide anions include Br / I.

[0075] As used herein, the term "metal halide perovskite" refers to a perovskite whose formula comprises at least one metal cation and at least one halide anion. As used herein, the term "organometallic halide perovskite" refers to a metal halide perovskite whose formula comprises at least one organic cation.

[0076] The term "organic cation" refers to a cation that contains carbon. The cation may contain other elements, for example, the cation may contain hydrogen, nitrogen or oxygen. The term "inorganic cation" refers to a cation that is not an organic cation. By default, the term "inorganic cation" refers to a cation that does not contain carbon.

[0077] As used herein, the term "n-type" refers to a region, layer or material containing an extrinsic semiconductor having a greater concentration of electrons than holes. Therefore, in an n-type semiconductor, electrons are majority carriers and holes are minority carriers, so they are electron transport materials. Therefore, as used herein, the term "n-type region" refers to a region of one or more electron transport (i.e., n-type) materials. Similarly, the term "n-type layer" refers to a layer of electron transport (i.e., n-type) materials. The electron transport (i.e., n-type) material can be a single electron transport compound or elemental material, or a mixture of two or more electron transport compounds or elemental materials. The electron transport compound or elemental material can be undoped or doped with one or more dopant elements or compounds.

[0078] As used herein, the term "p-type" refers to a region, layer or material containing an extrinsic semiconductor having a greater concentration of holes than electrons. In a p-type semiconductor, holes are the majority carriers and electrons are the minority carriers, so they are hole transport materials. Therefore, as used herein, the term "p-type region" refers to a region of one or more hole transport (i.e., p-type) materials. Similarly, the term "p-type layer" refers to a layer of hole transport (i.e., p-type) materials. The hole transport (i.e., p-type) material can be a single hole transport compound or elemental material, or a mixture of two or more hole transport compounds or elemental materials. The hole transport compound or elemental material can be undoped or doped with one or more dopant elements or compounds.

[0079] As used herein, the term "layer" refers to any structure that is substantially laminar in form (e.g., substantially extending in two perpendicular directions, but whose extension in a third perpendicular direction is limited). A layer may have a thickness that varies over the range of the layer. Typically, a layer has an approximately constant thickness. As used herein, the "thickness" of a layer refers to the average thickness of the layer. The thickness of a layer can be readily measured, for example, by using microscopic examination, such as electron microscopy of a cross section of a film, or by surface profile measurement, for example, using a stylus profilometer.

[0080] Reaction method

[0081] The present invention relates to a method for preparing a 3D organic-inorganic hybrid halide perovskite material, which involves converting a 2D organic-inorganic hybrid halide perovskite material into a desired 3D perovskite material. Preferably, the 3D perovskite is a highly crystalline material. Further preferably, the resulting 3D perovskite material is suitable for use as a high-quality photovoltaic absorber material.

[0082] Figure 2A-2B A schematic diagram showing several possible method flows of the method according to the present invention, and Fig.14One of these method flows for the overall reaction method of the present invention is shown and compared to the prior art path. The method of the present invention involves forming a layer of 2D perovskite material on a substrate and subjecting the 2D perovskite material layer to a reaction step to convert the 2D perovskite material into a 3D perovskite analog.

[0083] In its broadest aspect, the present invention provides a method of forming a crystal or polycrystalline layer of an organic-inorganic metal halide perovskite material comprising a three-dimensional crystal structure represented by the formula AMX3,

[0084] wherein A represents an organic cation or a mixture of two or more different cations, at least one of which is an organic cation,

[0085] M represents a divalent metal cation or a mixture of two or more different divalent metal cations,

[0086] and X represents the same or different halide anions,

[0087] The method comprises the following steps:

[0088] (i) forming a first layer on a surface of a substrate, the first layer comprising an organic-inorganic metal halide perovskite material having a planar, layered, two-dimensional crystal structure

[0089] (ii) reacting the first layer with one or more organic halides to form a crystalline or polycrystalline layer comprising an organic-inorganic metal halide perovskite material having the formula AMX3.

[0090] There are a variety of methods for forming a first layer comprising an organic-inorganic metal halide perovskite material having a planar, layered, two-dimensional crystal structure. In one aspect, the present invention provides a method for forming a crystalline or polycrystalline layer of an organic-inorganic metal halide perovskite material comprising a three-dimensional crystal structure represented by the formula AMX3, wherein A represents one or more cations that are the same or different, at least one comprising an organic cation, M represents a mixture of one or more divalent metals, and X is a halide anion that is the same or different, the method comprising the steps of:

[0091] forming a first layer on a surface of a substrate, the first layer comprising an organic-inorganic halide perovskite material having a planar, layered, two-dimensional crystal structure;

[0092] depositing a material comprising one or more organic halides on said first layer; and

[0093] • reacting the first layer and the mixture deposited thereon to form a polycrystalline layer comprising an organic-inorganic metal halide perovskite material having the formula AMX3 as defined above.

[0094] In other words, in the method of the present invention, step (ii) comprises

[0095] a) depositing a material comprising one or more organic halides on said first layer; and

[0096] b) reacting the first layer and a material deposited thereon to form a crystalline or polycrystalline layer comprising an organic-inorganic metal halide perovskite material having the formula AMX3.

[0097] In other embodiments, there is no separate step of depositing a material comprising one or more organic halides on the first layer. The organic halide may already be present when performing step (i), so that a separate addition of the organic halide is not required. Figure 2B Shown in.

[0098] In step i), the two-dimensional crystal structure generally has the general formula L2MX4, where L is a ligand that does not appear in the final perovskite product. Preferably, L is an organic or inorganic cation or a mixture of organic or inorganic cations that may be the same or different, M is a divalent metal cation or a mixture of two or more different divalent metal cations. X is one or more different halide anions.

[0099] Preferably, the 2D material has the formula L2L' n-1 M n X 3n+1 or L2K n-1 M n X 3n+3 or LL' n-1 M n X 3n+1 or L2L' n M n X 3n+2 , wherein L and L' represent organic or inorganic cations which may be the same or different, K represents an organic cation different from L, M represents one or more divalent metals, and X represents one or more different halide anions.

[0100] Ideally, the 3D organic-inorganic hybrid halide perovskite is substantially free of 2D perovskite material. By this, we mean that the 3D organic-inorganic hybrid halide perovskite product layer typically contains less than 5 wt%, preferably less than 2 wt%, and even more preferably less than 1 wt% of 2d perovskite material.

[0101] Step (i) of forming a first layer of a two-dimensional organic-inorganic hybrid halide perovskite as described above on a substrate may be achieved using any convenient method. Suitable methods include, but are not limited to: i) physical or chemical vapor deposition, ii) deposition from solution (which may optionally include spin coating or dip coating techniques), and iii) deposition of a precursor compound, such as one or more metal halides, by physical vapor deposition or from solution, followed by conversion of the precursor compound to the desired L2MX4 material.

[0102] The first step in the reaction process can be represented by the general reaction scheme:

[0103] MX2+2LX→L2MX4

[0104] In a first method according to the invention, the first layer is formed by physical or chemical vapor deposition of a 2D-perovskite material.

[0105] In an alternative method of the invention, the first layer is formed by depositing a 2D perovskite material from solution.

[0106] In another alternative method according to the invention, the first layer is formed by physical vapor deposition of a precursor layer comprising at least one metal halide precursor material, followed by conversion of the precursor layer into a first layer comprising a 2D perovskite material.

[0107] In a variation of the above alternative method, the first layer is formed by solution deposition of a precursor layer comprising at least one metal halide precursor material, followed by conversion of the precursor layer into a first layer comprising a 2D perovskite material.

[0108] The first layer of the two-dimensional organic-inorganic hybrid halide perovskite may comprise a plurality of 2D perovskite layers of any structural form. Preferably, the structural form will be of the type discussed in the introduction, such as a "Ruddelsden-Popper perovskite", which preferably adopts the general formula A n-1 A2'M n X 3n+1 ; "{110} parallel perovskite", which preferably adopts the general formula A'2A n M n X 3n+2 ; "Aurivillius perovskite", which preferably adopts the general formula A'2A n-1 M n X 3n+3 and "Dion-Jacobson perovskites", which preferably have the general formula CA n- 1M n X 3n+1 Examples of each of these families for n = 2 are given in Figure 4 Shown in.

[0109] It is particularly preferred that the first layer of the two-dimensional organic-inorganic hybrid halide perovskite comprises a plurality of 2D perovskite layers which adopt at least one of: a Ruddelsden-Popper structural form, a structural form similar to or derived from the Ruddelsden-Popper form, and a structural form that produces a 2D perovskite that behaves in the same or substantially similar manner as those of the Ruddelsden-Popper or similar structural forms.

[0110] In a specific embodiment, A and L' represent the same cation present in the final 3D layer and are selected from: Cs, Rb, methylammonium, ethylammonium, formamidinium or guanidinium.

[0111] L is a cation in the initial 2D precursor layer but not in the final 3D layer and is selected from: Cs, Rb, formamidinium, guanidinium or an organic ion R3NH + , wherein R is selected from H, an unsubstituted or substituted aryl group or an unsubstituted or substituted alkyl group, such as methylammonium or ethylammonium. Specific examples include: -phenethylammonium, n-propylammonium, n-butylammonium, n-pentylammonium, n-hexylammonium, n-heptylammonium, n-octylammonium, naphthylethylammonium, 2-(2-naphthyl)ethananammonium, benzylammonium, phenylammonium, 2-thiopheneethylammonium, tert-butylammonium, diethylammonium, isobutylammonium, cyclohexylammonium, cyclohexylmethylammonium, ethylammonium, 1,4-butanediammonium, 2,2'-dithiobis(ethylammonium), 3-(aminomethyl)piperidine, 4-(aminomethyl)piperidine, 2-(4-biphenyl)ethylammonium, 1,4-butanediamine, 1,5-pentanediamine, 1,6-hexanediamine, 1,7-heptanediammonium, 1,8-octanediamine, 1,9-nonanediammonium, 1,4-phenylenediamine, and 4-methoxy-phenethylammonium.

[0112] K is another cation in the initial 2D layer but not in the final 3D layer and has the formula H + R2NR'NR2H + , wherein R is selected from H, an unsubstituted or substituted aryl group or an unsubstituted or substituted alkyl group, and R' may be an unsubstituted or substituted aryl group or an unsubstituted or substituted alkyl group.

[0113] In step ii) of the method according to one aspect of the invention, when depositing a material comprising one or more halides on the first layer, the first layer may be exposed to a vapor comprising organic halides AY and AZ, wherein Y and Z are identical or different halide anions, and cations A are identical or different and are selected from cations of the following metals: Cs, Rb, formamidinium, guanidinium or an organic ion R3NH +, wherein R is selected from H, an unsubstituted or substituted aryl group or an unsubstituted or substituted alkyl group, or H + R2NR'NR2H + , wherein R can be H, an unsubstituted or substituted aryl group, or an unsubstituted or substituted alkyl group, and R' can be an unsubstituted or substituted aryl group, or an unsubstituted or unsubstituted alkyl group. In the final 3D perovskite product, the Y and Z halide anions become anions represented by the group X.

[0114] Preferred groups for the A group in the halides AY and AZ correspond to those listed above for the final AMX3 perovskite product.

[0115] Step ii) of the reaction according to the present invention can be represented by a general reaction scheme:

[0116] L2MX4+AY+AZ→AMXZY

[0117] Step ii) of the reaction according to the present invention is usually carried out by heating to a temperature of less than 200 degrees Celsius, preferably by heating to a temperature of 100 to 180 degrees Celsius. Example

[0118] Figure 2A-2B An overview of the reaction scheme for the process of the invention is given.

[0119] Example 1(a) - Formation of [FA]PbI2Br

[0120] (a). A 300 nm thick layer of PbI2 is evaporated onto a glass substrate. A solution of phenethylammonium iodide (PEAI) dissolved in 1-methoxy-2-propanol (PGME) is made, containing 10 wt% PEAI and filtered through a 0.2 μm filter. The solution is then spin-coated onto the layer of PbI2, typically at a rotation speed of 7000 rpm in an air environment. The substrate is then transferred to an oven and baked at 90°C for 30 minutes. This forms a first layer comprising an organic-inorganic halide perovskite material having a planar, layered, two-dimensional crystal structure and having the formula (PEA)2PbI4, wherein the planar layers are oriented perpendicular to the normal to the substrate surface. The layer will be about 400 nm thick.

[0121] (b). Prepare a solution of formamidinium iodide (FAI) and formamidinium bromide (FABr) dissolved in anhydrous isopropyl alcohol (IPA), wherein the solution contains 5% by weight of solids and the molar ratio of FAI:FABr is 0.7:1. The solution is filtered through a 0.2 μm filter and spin-coated onto the first layer prepared in step (a) above at a rotation speed of 5000 rpm in a dry nitrogen environment. The substrate is then transferred to a hot plate and baked at 50°C for 1 minute, then transferred to an oven and baked at 160°C for 60 minutes. This forms a layer of a material having a three-dimensional perovskite structure of the formula [FA]PbI2Br. The layer will be about 400 nm thick.

[0122] Example 1(b) - Formation of [FA]PbI2Br

[0123] The method is as described above, but the initial layer of PbI2 is deposited from solution.

[0124] Example 2 - [FA] (1-x) Cs (x) Formation of PbI2Br

[0125] (a). A 300 nm thick layer comprising a mixture of PbI2 and CsI is deposited on a glass substrate by co-evaporation. Depending on the target composition of the final 3D perovskite, the mixture is controlled to have a desired Cs:Pb molar ratio. A solution of phenethylammonium iodide (PEAI) dissolved in 1-methoxy-2-propanol (PGME) is made, containing 10 wt% PEAI and filtered through a 0.2 μm filter. The solution is then spin-coated onto the layer of PbI2+CsI, typically at a rotation speed of 7000 rpm in an air environment. The substrate is then transferred to an oven and baked at 90°C for 30 minutes. This forms a first layer comprising an organic-inorganic halide perovskite material having a planar, layered, two-dimensional crystal structure and having the formula ((PEA) 1-x Cs (x) )PbI4, where the planar layer is oriented perpendicular to the normal to the substrate surface. This layer will be about 400nm thick.

[0126] (b) Prepare a solution of formamidinium iodide (FAI) and formamidinium bromide (FABr) dissolved in anhydrous isopropyl alcohol (IPA) containing 5 wt% solids and a molar ratio of FAI:FABr of 0.7:1. Filter the solution through a 0.2 μm filter and spin-coat it onto the first layer prepared in step (a) above at a rotation speed of 5000 rpm in a dry nitrogen environment. The substrate is then transferred to a hot plate and baked at 50°C for 1 minute, then transferred to an oven and baked at 160°C for 60 minutes. This forms a substrate having the formula [FA] (1-x) Cs (x) A layer of material with a three-dimensional perovskite structure of PbI2Br. This layer will be about 400nm thick.

[0127] Example 3 - Formation of [MA]PbI2Br

[0128] (a). A 300 nm thick layer of PbI2 is evaporated onto a glass substrate. A solution of phenethylammonium iodide (PEAI) dissolved in 1-methoxy-2-propanol (PGME) is made, containing 10 wt% PEAI and filtered through a 0.2 μm filter. The solution is then spin-coated onto the layer of PbI2, typically at a rotation speed of 7000 rpm in an air environment. The substrate is then transferred to an oven and baked at 90°C for 30 minutes. This forms a first layer comprising an organic-inorganic halide perovskite material having a planar, layered, two-dimensional crystal structure and having the formula (PEA)2PbI4, wherein the planar layers are oriented perpendicular to the normal to the substrate surface. The layer will be about 400 nm thick.

[0129] (b). Prepare a solution of methylammonium iodide (MAI) and methylammonium bromide (MABr) dissolved in anhydrous isopropyl alcohol (IPA), wherein the solution contains 5% by weight of solids and the molar ratio of MAI:MABr is 0.7:1. Filter the solution through a 0.2 μm filter and spin-coat it onto the first layer prepared in step (a) above at a rotation speed of 5000 rpm in a dry nitrogen environment. The substrate is then transferred to a hot plate and baked at 50°C for 1 minute, then transferred to an oven and baked at 160°C for 60 minutes. This forms a layer of material having a three-dimensional perovskite structure of the formula [MA]PbI2Br. The layer will be about 400 nm thick.

[0130] Example 4

[0131] In an alternative embodiment, in which the planar layers are oriented perpendicular to the normal to the substrate surface mentioned in step (a) of Examples 1 to 3 above, a first layer comprising an organic-inorganic halide perovskite material having a planar, layered, two-dimensional crystal structure can be grown directly from the vapor phase, for example, as described in Masanao Era et al., "Self-Organised Growth of PbI-based Layered Perovskite Quantum Well by Dual-Source Vapour Deposition", Chem. Mater. Vol. 9, No. 1, pp. 8–10

[1997] .

[0132] Example 5

[0133] In the above examples 1 to 3, organic halides (FAI and FABr) can be added to the initial reaction mixture together with PEAI. Therefore, the organic halides are not added in a separate step (b). Both the organic halides and PEAI are transferred to the metal halide film, and a two-dimensional perovskite structure is formed in situ with FA. The 3D perovskite structure is formed by heating in the same manner as described in the above examples.

[0134] Example 6

[0135] 18 functional devices were constructed and tested as described below. The devices were divided into two groups: the first group had a perovskite layer prepared according to the 2-D method of the present invention as described in Example 2 above, and the second group had a perovskite layer prepared according to the two-step method of the prior art.

[0136] The devices were nip single junctions built on glass substrates and contacted with gold electrodes. The device structures used in both groups were identical, with only the perovskite deposition changed. The devices were exposed to simulated AM1.5 sunlight (1-sun, 100 mW cm) generated by an ABET-grade AAB Solar 2000 simulator. -2 ) in ambient air. The solar simulator was calibrated for 1.6 eV perovskite bandgap using a certified KG3 filtered silicon reference cell. Each device was measured using a Keithley 2400 source meter with a 20 mV voltage step. All devices were measured with a 0.0919 cm 2 Metal hole masking to define the active area and eliminate edge effects.

[0137] The average efficiency per share of 18 functional devices is 14.84 for the 2-step method and 15.93 for the 2D method of the present invention.

[0138] The following table shows the extracted parameters and comparative data, where these numbers are from Fig.13 Figure in:

[0139] 2D Path 2-step method η(%) 17.3 16.7 <![CDATA[V oc (V)]]> 1.13 1.10 FF(%) 78.8 79.3 <![CDATA[J sc (mA cm -2 )]]> 19.43 19.19

[0140] Data such as Fig.13 As shown, the figure shows the current-voltage scans of single junction devices prepared via the 2D route and the 2-step method, where we see a gain in Voc via the 2D route, which is expected from a higher photoluminescence quantum efficiency (PLQE).

Claims

1. A method for forming a crystalline layer of an organic-inorganic metal halide perovskite material, wherein the organic-inorganic metal halide perovskite material comprises a three-dimensional crystal structure represented by the formula AMX3, wherein A represents an organic cation or a mixture of two or more different cations, at least one of which is an organic cation, M represents a divalent metal cation or a mixture of two or more different divalent metal cations, and X represents the same or different halide anions, The method comprises the following steps: (i) forming a first layer on a surface of a substrate, the first layer comprising an organic-inorganic metal halide perovskite material having a planar, layered two-dimensional crystal structure, (ii) reacting the first layer with one or more organic halides to form a crystalline layer comprising an organic-inorganic metal halide perovskite material having the formula AMX3.

2. The method for forming a crystalline layer of an organic-inorganic metal halide perovskite material according to claim 1, wherein: Step (ii) comprises a) depositing a material comprising one or more organic halides on the first layer; and b) reacting the first layer with a material deposited thereon to form a crystalline layer comprising an organic-inorganic metal halide perovskite material having the formula AMX3.

3. The method according to claim 1 or 2, wherein In step (i), the first layer comprises a material having a formula selected from the group consisting of: L2L' n-1 M n X 3n+1 、L2K n-1 M n X 3n+3 LL' n-1 M n X 3n+1 or L2L' n M n X 3n+2 , wherein L and L' represent the same or different organic or inorganic cations, K represents an organic cation and is different from L, M represents a divalent metal cation or two or more different divalent metal cations, and X represents the same or different halide anions.

4. The method according to claim 3, wherein: L, L' and K are independently selected from the group consisting of naphthylethylammonium, n-propylammonium, benzylammonium, phenylammonium, n-pentylammonium, 2-thienylethylammonium, tert-butylammonium, diethylammonium, isobutylammonium, cyclohexylammonium, cyclohexylmethylammonium, ethylammonium, 1,4-butanediammonium and cystamine dihydride.

5. The method according to claim 1 or 2, wherein The first layer is formed by physical or chemical vapor deposition of an organic-inorganic metal halide perovskite material having a planar, layered, two-dimensional crystal structure.

6. The method according to claim 1 or 2, wherein: The first layer is formed by depositing an organic-inorganic metal halide perovskite material from solution.

7. The method according to claim 1 or 2, wherein The first layer is formed by depositing a precursor material comprising one or more metal halide materials on the surface of the substrate, and then converting the precursor material comprising one or more metal halide materials into a first layer comprising the organic-inorganic metal halide perovskite material having a planar, layered two-dimensional crystal structure.

8. The method according to claim 7, wherein The precursor material comprising one or more metal halide materials is converted into the first layer by depositing one or more organic halide materials onto the precursor material comprising one or more metal halide materials and reacting the one or more organic halide materials and the precursor material comprising one or more metal halide materials to form a first layer comprising the organic-inorganic metal halide perovskite material having a planar, layered two-dimensional crystal structure.

9. The method according to claim 8, wherein: The one or more organic halide materials are selected from: naphthylethylammonium iodide, n-propylammonium iodide, benzylammonium iodide, phenylammonium iodide, n-pentylammonium iodide, 2-thienylethylammonium iodide, tert-butylammonium iodide, diethylammonium iodide, isobutylammonium iodide, cyclohexylammonium iodide, cyclohexylmethylammonium iodide, ethylammonium iodide, 1,4-butanediammonium diiodide and cystamine dihydroiodide.

10. The method according to claim 1 or 2, wherein: The first layer is formed by depositing a precursor material comprising one or more organic halide materials on the surface of the substrate, then depositing one or more metal halide materials, and then converting the precursor material comprising one or more organic halide materials and the one or more metal halide materials into a first layer comprising the organic-inorganic metal halide perovskite material having a planar, layered two-dimensional crystal structure.

11. The method according to claim 10, wherein: The precursor material comprising one or more organohalide materials is deposited from solution.

12. The method according to claim 8, wherein: The one or more organohalide materials are deposited onto the precursor material comprising the one or more metal halide materials from a solution of one or more organoammonium halides dissolved in a solvent, and the solvent is then removed.

13. The method according to claim 12, wherein: The solvent comprises one or more solvents selected from 1-butanol, 1-propanol, isopropanol, 1-methoxy-2-propanol, 2-methoxy-methanol, 2-ethoxy-ethanol, ethylene glycol mono-tert-butyl ether and toluene.

14. A method according to claim 12 or 13, wherein The organic ammonium halide is selected from the group consisting of naphthylethylammonium iodide, n-propylammonium iodide, benzylammonium iodide, phenylammonium iodide, n-pentylammonium iodide, 2-thienylethylammonium iodide, tert-butylammonium iodide, diethylammonium iodide, isobutylammonium iodide, cyclohexylammonium iodide, cyclohexylmethylammonium iodide, ethylammonium iodide, 1,4-butanediammonium diiodide and cystamine dihydroiodide.

15. The method according to claim 1 or 2, wherein: M comprises one or more metals selected from the group consisting of Pb, Sn, Sb and Cu.

16. The method according to claim 2, wherein: The material comprising one or more organic halides in step a) is deposited by exposing the first layer to a vapor comprising halides AY and AZ, wherein Y and Z are the same or different halide anions, and cations A are the same or different and are selected from cations of the following metals or the following organic cations: Cs, Rb, formamidinium, guanidinium or an organic ion R3NH + , wherein R is selected from H, an unsubstituted or substituted aryl group or an unsubstituted or substituted alkyl group, or H + R2NR'NR2H + , wherein R is H, an unsubstituted or substituted aryl group, or an unsubstituted or substituted alkyl group, and R' is an unsubstituted or substituted aryl group, or an unsubstituted or substituted alkyl group.

17. The method according to claim 2, wherein: The material comprising one or more organic halides in step a) is deposited from a solution of halides AY and AZ, wherein Y and Z are the same or different halide anions, and cation A is the same or different and is selected from the following metal cations or the following organic cations: Cs, Rb, formamidinium, guanidinium or the organic ion R3NH + , wherein R is selected from H, an unsubstituted or substituted aryl group or an unsubstituted or substituted alkyl group, or H + R2NR'NR2H + , wherein R is H, an unsubstituted or substituted aryl group, or an unsubstituted or substituted alkyl group, and R' is an unsubstituted or substituted aryl group, or an unsubstituted or substituted alkyl group.

18. The method according to claim 1 or 2, wherein: The reaction in step (ii) is achieved by heating above room temperature.

19. The method according to claim 18, wherein: The heating is performed at a temperature less than 200 degrees Celsius.

20. The method according to claim 19, wherein: The heating is performed at a temperature of 100 to 180 degrees Celsius.

21. The method according to claim 1 or 2, wherein: The crystalline layer is a polycrystalline layer.

22. A method for preparing a photovoltaic device comprising an active layer, wherein the active layer comprises an organic-inorganic metal halide perovskite material, wherein the organic-inorganic metal halide perovskite material comprises a three-dimensional crystal structure represented by the formula AMX3, wherein A represents an organic cation or a mixture of two or more different cations, at least one of the mixture is an organic cation, M represents a divalent metal cation or a mixture of two or more different divalent metal cations, and X represents the same or different halide anions, wherein the method comprises forming the material comprising the active layer by a method according to any one of the preceding claims.

23. The method according to claim 22, wherein: The optoelectronic device is a photovoltaic device.

Citation Information

Patent Citations

  • Method of fabricating perovskite solar cell

    US20160049585A1

  • Formation of lead-free perovskite film

    US20180247769A1

  • Gas-induced perovskite formation

    WO2016194317A1

  • Two-step deposition process

    CN107075657A

  • Preparation method of Bi-based perovskite light absorption layer material

    CN108435514A